Regulatory Roles of Human Surfactant Protein B Variants on Genetic Susceptibility to Pseudomonas Aeruginosa Pneumonia-Induced Sepsis. Issue 4 (October 2020) - Yang, Fengyong; Zhang, Jing; Yang, Yi; Ruan, Feng; Chen, Xinghua; Guo, Junping; Abdel-Razek, Osama; Zuo, Yi Y.; Wang, Guirong
Abstract : ABSTRACT: Surfactant protein B (SP-B) is essential for life and plays critical roles in host defense and lowering alveolar surface tension. A single-nucleotide polymorphism (SNP rs1130866) of human SP-B (hSP-B) alters the N-linked glycosylation, thus presumably affecting SP-B function. This study has investigated the regulatory roles of hSP-B genetic variants on lung injury in pneumonia-induced sepsis. Methods: Wild-type (WT) FVB/NJ and humanized transgenic SP-B-T and SP-B-C mice (expressing either hSP-B C or T allele without mouse SP-B gene) were infected intratracheally with 50 μL (4 × 10 4 colony-forming units [CFUs]/mouse) Pseudomonas aeruginosa Xen5 or saline, and then killed 24 or 48 h after infection. Bacterial dynamic growths were monitored from 0 to 48 h postinfection by in vivo imaging. Histopathological, cellular, and molecular changes of lung tissues and bronchoalveolar lavage fluid (BALF) were analyzed. Surface tension of surfactants was determined with constrained drop surfactometry. Results: SP-B-C mice showed higher bioluminescence and CFUs, increased inflammation and mortality, the higher score of lung injury, and reduced numbers of lamellar bodies in type II cells compared with SP-B-T or WT ( P < 0.05). Minimum surface tension increased dramatically in infected mice ( P < 0.01) with the order of SP-B-C > SP-B-T > WT. Levels of multiple cytokines in the lung of infected SP-B-C were higher than those of SP-B-T and WT ( P < 0.01). Furthermore, compared with SP-B-T or WT, SP-B-C exhibited lower SP-B, higher NF-κB and NLRP3 inflammasome activation, and higher activated caspase-3. Conclusions: hSP-B variants differentially regulate susceptibility through modulating the surface activity of surfactant, cell death, and inflammatory signaling in sepsis.